Trithorax regulates long-term memory in Drosophila through epigenetic maintenance of mushroom body metabolic state and translation capacity. - Nicholas Raun; Spencer G Jones; Olivia Kerr; Crystal Keung; Emily F Butler; Kumari Alka; Jonathan D Krupski; Robert A Reid-Taylor; Veyan Ibrahim; MacKayla Williams; Deniz Top; Jamie M Kramer (PLoS Biology)
The role of epigenetics and chromatin in the maintenance of postmitotic neuronal cell identities is not well understood. Here, we show that the histone methyltransferase Trithorax (Trx) is required in postmitotic memory neurons of the Drosophila mushroom body (MB) to enable their capacity for long-term memory (LTM), but not short-term memory (STM). Using MB-specific RNA-, ChIP-, and ATAC-sequencing, we find that Trx maintains homeostatic expression of several non-canonical MB-enriched transcripts, including the orphan nuclear receptor Hr51, and the metabolic enzyme lactate dehydrogenase (Ldh). Through these key targets, Trx facilitates a metabolic state characterized by high lactate levels in MBγ neurons. This metabolic state supports a high capacity for protein translation, a process that is essential for LTM, but not STM. These data suggest that Trx, a classic regulator of cell type specification during development, has additional functions in maintaining underappreciated aspects of postmitotic neuron identity, such as metabolic state. Our work supports a body of evidence suggesting that a high capacity for energy metabolism is an essential cell identity characteristic for neurons that mediate LTM.